ChemInform Abstract: Decatungstate Photocatalyzed Benzylation of Alkenes with Alkylaromatics. Issue 16 (22nd April 2014) - Qrareya, Hisham; Ravelli, Davide; Fagnoni, Maurizio; Albini, Angelo
Abstract The direct benzylation of electrophilic alkenes with alkylbenzenes is achieved by decatungstate photocatalysis in a high ionic strength medium.